Novak: navigating identity in a commodified reality - Tan, Nicole YingLi (Nanyang Technological University, 2024)
The pervasive influence of capitalist structures, characterized by an extensive control over individuals and the commodification on of nearly all facets of existence, engenders a profound loss in the sense of authenticity and a pervasive alienation from our true selves. In an era of hyper-consumerism, the rise in privatised power over limited resources has led to an increase in isolation amongst individuals and an increase in incongruence in individuals’ self and conformity. This has led to a questioning of the sociological impacts of Late-Stage Capitalism. As such, there is a need to investigate the evolution of late-stage capitalism throughout history and the impacts of consumerism on individual identities.